(untitled) (Bangladesh Journal of Urology, 2020)
Objective: The objective of this article is to share our experience of Mini PCNL in horseshoe kidneys. Methods: We performed Mini PCNL in 05 patients with Horse shoe kidneys in theurology centre of CMH Dhaka. Per cutaneous puncture was made with patient in proneposition. Their ages ranged between 35-52 years with a mean age of 42.3 years. PCNLaccess tract was made in upper pole of the kidney in 03(60%) while 01(20%) throughmiddle calyx, and 01(20%) had direct pelvic access. The stone size was 2.3-2.75cm withmultiple calculi in two kidneys. Results: Complete Stone clearance was achieved in all 05 cases .Mean hospital stay was3.8 days (range 3-5 days).All cases were followed up at 4 weeks and after 3 months. Nosignificant Complications were seen except one patient who developed transient postoperativepyrexia which subsided with antipyretics. None of our patients developedpost PCNL bleeding or wound infection. Conclusion: Mini PCNL in horse shoe kidneys are not too difficult than normal kidneysand does not carry significant risk than reported for normal kidneys. This effectivemodality resulted in almost100% stone clearance with minimal morbidity. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.82-86